A study of turbulence in the Swedish payment system – Is there a way forward?. Issue 5 (19th August 2014) - Arvidsson, Niklas
Abstract : Purpose: The field of payments in Europe could benefit from renewal but is facing turbulence and great challenges concerning its future due to a variety of strong driving forces. This leads to uncertainty which makes actors – industrial as well as policy-making agencies – passive and reluctant to take needed steps that may realize a new playing field for payments. Design/methodology/approach: The article uses scenario analysis methodology to propose a way forward if the field of payments is to move away from turbulence and instead embrace renewal. It is based on a literature study, interviews and workshops. Findings: This article discusses and shows how the payment system is in a state of turbulence, which in itself may become a self-reinforcing negative process. The seemingly rational competitive actions that firms take in this situation may make the situation worse. The article also outlines critical action that must be taken to avoid this negative process. Research limitations/implications: There is a need for research that integrates studies on innovation and renewal in the critical industries – banking, telecom and the system driving industries – to improve our understanding of possible synergies and/or obstacles to integrated, cross-industry innovation efforts. Such insights may also lay the foundation for the creation of a way to overcome turbulence. Practical implications: The article advocates the need that critical actors collaborate to develop a new understanding – or common ground - of a future payment system. This will serve as a tool to identify obstacles and challenges, develop action and formulate agendas for different actors in and around the system. Based on the new common ground, actors are then free to formulate their own strategic agendas in a new competitive landscape in the field of payments. Originality/value: The originality of this paper is to test to the idea that turbulence and the consequential inertia in the payment system is a result of the institutional set-up of the industry. In addition, the article uses causal texture theory and scenario analysis to understand turbulence and inertia in the payment system. This has to my knowledge not been done before.